Geotechnical aspects of underground construction in soft ground : proceedings of the 6th International Symposium, (IS-Shanghai 2008), Shanghai, China, 10-12 April 2008 /: proceedings of the 6th International Symposium, (IS-Shanghai 2008), Shanghai, China, 10-12 April 2008. (©2009) - Unknown
No abstract available